Identifikasi Keanekaragaman dan Potensi Jenis-Jenis Ikan Air Tawar Pulau Bangka - Irma Akhrianti; Andi Gustomi (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2018)
Characteristics of Bangka Island which is an archipelago region with high economic potential of marine and fishery resources, it is deemed necessary to conduct research on the diversity of freshwater fish to support the increase of economic, ecological and conservation value of freshwater fish resources. Because of considering the research especially freshwater biodiversity of fish is seldom doing in Bangka Island, this research need to done. The aim of this research is to compile and identify the diversity of freshwater fish species in Bangka Island and to identify the potential utilization of freshwater fish species in Bangka Island based on the characteristics of dichromaticism and dimorphism. There are 63 species of 24 families of freshwater fish in the waters of Bangka Island. 2 unidentified fish species. Family Cyprinidae is the most caught type of 18 individuals. Fish potential analysis shows that there are 26 species of fish with potential for consumption, 33 species of fish have ornamental potential, 5 types of fish have ornamental potential and consumption, and 1 species of unidentified fish potential. Analysis of water quality in three observation streams indicates that water quality is still good for fish life